2018
DOI: 10.1007/s11892-018-1001-9
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Obesity in Adults: a Review of Recent Research and Future Directions

Abstract: Online patient communities for weight loss abound but may include misinformation. Systematic reviews and meta-analyses suggest that social media-delivered lifestyle interventions modestly impact weight, yet how social media was used and participant engagement varies widely. The rapidly changing social media landscape poses challenges for patients, clinicians, and researchers. Research is needed on how patients can establish supportive communities for weight loss and the role of clinicians in these communities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 82 publications
0
55
0
3
Order By: Relevance
“…337 Valuable smartphone functionalities include the ability to receive and analyse data from sensors measuring activity or biological variables; access health information via the internet; and engage with social media to promote lifestyle change. 338 Increasingly, consumers are able to access elements of their electronic health records via their smartphone or other portable device, providing an important opportunity for consumer partnership and empowerment. However, smartphones are more expensive than basic mobiles and require an internet connection, so text messaging may be required to provide broader population access in some low-income settings.…”
Section: Digital Technologies For People With Mental Illnessmentioning
confidence: 99%
“…337 Valuable smartphone functionalities include the ability to receive and analyse data from sensors measuring activity or biological variables; access health information via the internet; and engage with social media to promote lifestyle change. 338 Increasingly, consumers are able to access elements of their electronic health records via their smartphone or other portable device, providing an important opportunity for consumer partnership and empowerment. However, smartphones are more expensive than basic mobiles and require an internet connection, so text messaging may be required to provide broader population access in some low-income settings.…”
Section: Digital Technologies For People With Mental Illnessmentioning
confidence: 99%
“…In fact, nearly 90% of social media users aged 50 or older use Facebook and/or Twitter to find and share health information, and women are nearly three times more likely than men to seek health information on social media (18). Weight loss interventions using Facebook as a primary delivery modality for young adults have been found to be acceptable and feasible (19) but it remains unknown whether this type of program is appropriate for adult female cancer survivors, of whom 87% are at least 50 years old (2). However, acceptability and effectiveness of technology-based interventions for weight loss (20,21) and increasing physical activity (22) in older cancer survivors has been established.…”
Section: Original Articlementioning
confidence: 99%
“…For example, some studies focused on how patients would discuss information found online during interactions with their healthcare providers [6]. Recent research examined the impact of mobile and social media on health communication across a variety of health topics, such as the impact of online support groups for breast cancer survivors, and the use of mHealth to deliver lifestyle interventions and social support for weight loss [7,8].…”
Section: The Rise Of Peer-to-peer Communicationmentioning
confidence: 99%
“…Rather, health literacy encompasses the capacity to comprehend the information provided and the ability to act on that information to improve health outcomes [16,17]. The rise of peer-to-peer platforms has helped limited literacy individuals overcome traditional barriers related to accessing health information [8]. However, in doing so, new health literacy challenges have been introduced, including the added challenge of evaluating peer-provided health information.…”
Section: Health Literacy In the Context Of Online Peer-to-peer Communmentioning
confidence: 99%